Long and winding roads the evolving artistry of the Beatles - Womack, Kenneth (Bloomsbury Academic, 2023)
"A follow-up to the successful 2007 edition, which, despite numerous Beatles-related books published in the intervening years, still stands alone for its chronological, album-by-album analysis of the band's work"--Provided by publisher.